Testosterone Undecanoate Hormone Microemulsion Formulation Optimization - Javier Desmond; Rorger tu Bam (Institute of Accounting Research and Novation (IARN), 2022)
Testosterone undecanoate, sometimes known as TU, is a medication that is hydrophobic. A microemulsion is a type of dispersion system that can boost the medications' solubility, especially those that are hydrophobic. In this investigation, the optimization of microemulsion formulations was carried out using a wide variety of surfactants, oils, cosurfactants, and water in their respective proportions. After that, a microemulsion was created with the following components: 30% tween 80 and 10% tween 20 as surfactant components, 24% isopropyl myristate (IPM) and 24% castor oil (CO) as oil phase, 10% n-butanol as a cosurfactant, and 2% water. The oil phase consisted of isopropyl myristate and castor oil. The findings obtained from the TU After being stored at 4o C and 27o C for two months, the examination of the microemulsion revealed that it remained in a stable condition